Trends in abundance and wintering phenology of the Dark-bellied Brent Goose Branta b. bernicla in France between 1982 and 2012 - Valéry, Loïc; Schricke, Vincent (Wildfowl, 2013)
Trends in abundance, the timing of arrival and departure, and the number of goose-daysÂ at internationally important sites, are presented for Dark-bellied Brent GeeseÂ Branta bernicla bernicla wintering in France during 1982â€“2012 inclusive. NumbersÂ wintering in France increased more rapidly than the increase in the population as aÂ whole: c. 30% of the world population occurred in France in 1982 and just over halfÂ in 2012. Throughout the past 30 years, c. 75% of Brent Geese wintering in France haveÂ concentrated at just six sites. Two of them (Bassin dâ€™Arcachon and Golfe duÂ Morbihan) have shown a sharp rise in numbers in mid-January, most notably a fivefoldÂ increase in 30 years at the Bassin dâ€™Arcachon, which now accounts for c. 43% of theÂ total in France (compared with c. 21% in 1982) and c. 22% of the world populationÂ (c. 5% in 1982). Wintering phenology at the six main sites, determined from the datesÂ on which 50% of the annual peak count had arrived and departed, has varied overÂ time. At five of the sites, this proportion of Brent Geese now arrives 3â€“4 weeks earlierÂ than 30 years ago. The total number of goose-days has increased almost fivefold atÂ Bassin dâ€™Arcachon and doubled in Baie de Bourgneuf, although the reasons for theseÂ changes remain unclear. In particular, the increase at Bassin dâ€™Arcachon meritsÂ investigation, given a long-term decline in eelgrass Zostera sp. abundance at this site.